Investigations of milk-fat lamb production practices for Western Kansas, Colby - Menzies, C.S.; Banbury, Evans E.; Elliott, H. (Kansas Agricultural Experiment Station, 2011)
The ewe flock is handled in an early-lambing program with the breeding season beginning June 1 and terminating September 1. Lams are creep-fed and sold as milk-fat lambs during spring and early summer. Three separate tests are conducted during the year. (1) The effects of varying levels of energy intake by ewes, during a preflushing period, on lambing performance. (2) Testing various rations for flushing ewes and ration effects on lambing performance. (3) A study of different management practices and rations for creep-feeding lambs.
Keywords: Sheep; Milk-fat lambs; Energy intake; Performance